(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
This research aimed to identify the reality of occupational health among primary school teachers in Latakia city from an ergonomic perspective and to measure differences in their viewpoints according to gender, educational qualification, and years of experience. To achieve objectives, the descriptive method was used through questionnaire consisting of (33) statements distributed across five axes: physical health, mental health, school work environment, ergonomic organization of work, and ergonomic awareness. The research sample consisted of (309) male and female teachers. The research reached the following results: - The reality of physical health, mental health, and the reality of the school work environment came at an average level in general, with relative importance reaching (66.8%), (63.8%), and (67.4%) respectively, while the reality of ergonomic organization and ergonomic awareness came at a high level, with relative importance reaching (75.8%) and (69.6%) respectively. - There were no statistically significant differences attributable to the variables of gender (male, female), educational qualification (intermediate institute, university degree, vocational diploma, postgraduate studies), and years of experience (less than 5 years, 5-10 years, 11-20 years, more than 20 years).